Extreme teams : why Pixar, Netflix, AirBnB, and other cutting-edge companies succeed where most fail /: why Pixar, Netflix, AirBnB, and other cutting-edge companies succeed where most fail. (2017) - Shaw, Robert Bruce
No abstract available